FIELD MEASUREMENT OF AIRBORNE SOUND INSULATION BETWEEN ROOMS - Jason Obadiah (Universitas Multimedia Nusantara, 2019)
Airborne sound can be a nuisance and a constant expose to the sound can in- troduced health problems to the people in the area especially areas where quiet environ- ment is a necessity. The objective of this measurement is to demonstrate the field mea- surement of the airborne sound insulation properties of interior walls. The measurement was done for determining the sound insulation properties of a partition between two rooms. This measurement will also determine the parameters and source of the prob- lems which are contributing to the airborne sound from the adjacent room. The results are that the volume of the room and the construction of the room (pipe construction and ceiling, etc.) have large effects to the sound transmitted between the rooms.